Islam dan Budaya dalam Harmoni - Idhar, Idhar (Peneliti.net, 2026)
Islam in the Archipelago is a form of Islam that developed by prioritizing local values and local culture, thus presenting a peaceful, moderate and inclusive face of Islam. This research aims to reveal and analyze the values of Islamic teachings that developed in the archipelago, as well as its distinctive and effective methods of dissemination. The method used is a qualitative approach with a type of library research, which is analyzed descriptively. The results show that the main values contained in the Nusantara Islamic teachings include tawazun (balance), tasamuh (tolerance), and tawassuth (moderation), all of which are rooted in Islamic teachings but packaged in the context of local culture. The method of spreading Islam is through education, marriage, and cultural acculturation, which makes Islam easily accepted by multicultural communities. Islam Nusantara is a contextual model of Islam, able to answer the challenges of the times, and strengthen the Islamic and national identity of Indonesian society.